Barriers in growth of Daraz Bangladesh from customer’s point of view : how to make the online shopping experience better - Ashraf, Syeda Sefat (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.